2013
DOI: 10.1111/head.12150
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Prevalence, Symptoms, and Associated Features of Migraine, Probable Migraine and Other Severe Headache: Results of the American Migraine Prevalence and Prevention (AMPP) Study

Abstract: Background.-The strikingly higher prevalence of migraine in females compared with males is one of the hallmarks of migraine. A large global body of evidence exists on the sex differences in the prevalence of migraine with female to male ratios ranging from 2 : 1 to 3 : 1 and peaking in midlife. Some data are available on sex differences in associated symptoms, headache-related disability and impairment, and healthcare resource utilization in migraine. Few data are available on corresponding sex differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
316
6
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(357 citation statements)
references
References 53 publications
28
316
6
7
Order By: Relevance
“…This is in contrast with migraine, as males proportionally have more often migraine with aura than females 6, 23. We found no difference in migraine comorbidity between cluster headache participants with and without typical aura.…”
Section: Discussioncontrasting
confidence: 71%
“…This is in contrast with migraine, as males proportionally have more often migraine with aura than females 6, 23. We found no difference in migraine comorbidity between cluster headache participants with and without typical aura.…”
Section: Discussioncontrasting
confidence: 71%
“…Data comparing the symptom severity between men and women show that women experience aura more commonly and have a greater impairment than males. [33] It is possible that women experience migraine symptoms more severely and are thus triaged more urgently.…”
Section: Triagementioning
confidence: 99%
“…Even though many studies report the same average pain intensity between sexes, women consistently report higher headache-related disability than do men [30,[43][44][45]. European studies have shown higher MIDAS scores and higher disability in women, but sex differences in the individual criteria have not been reported [17,45,46,47].…”
Section: Specific Disabilitiesmentioning
confidence: 98%
“…Research suggests that women have more frequent, longer lasting, and more severe headaches than men [15] although some studies show that Pain intensity and attack frequency tend to be similar in men and women [16].…”
Section: Clinical Featuresmentioning
confidence: 99%